In vitro antimicrobial activity screening of tropical medicinal plants used in Santo Domingo, Dominican Republic. Part I. - M. Lozano, Cesar; Vasquez-Tineo, Manuel A.; Ramirez, Maritza; Jimenez, Francisco (Pharmacognosy Communications)
Introduction: Very little is known on the uses of medicinal plants in the Caribbean island of Dominican Republic. There is a lack of scientific data supporting medicinal plant uses. The objective of the present study was to evaluate the antimicrobial activity of crude extracts of 50 medicinal plants collected from vendors at regional or municipal markets and that are used in the treatment of several types of infections in Dominican Republic. Methods: Ethanolic plant extracts were tested against five microorganisms species - Escherichia coli, Klebsiella pneumoniae, Staphylococcus aureus, Pseudomona aeruginosa, and Candida albicans using the disc diffusion method. Extracts were inoculated onto discs and placed on agar plates spread with microorganisms using sterile swabs. Following 24 hours of incubation at37°C, the plates were analyzed and the zones of inhibition measured. Results and Discussion: Fourty-four of the plants tested showed inhibitory activity against one or more of the microorganisms at a 35 μg/mL extract concentration. Plants exhibiting the widest antimicrobial activity were Inga vera, Ruellia tuberosa, Calophyllum calaba, and Merremia dissecta, and were effective on at least three out the four of the bacteria tested. The test antibiotics Amikacin and Norfloxacin showed strong inhibitory activities against all bacteria but only low activity against Klebsiella pneumonia. Very few extracts showed antifungal activity against Candida albicans, however higher activity was found using Cardiospermum halicacabum extract. Conclusions: Several ethanolic extracts derived from plants used in traditional medicine in Dominican Republic possess significant antimicrobial activity against a variety of the tested microorganisms, although the mechanism(s) of action require further study.
Keywords: Ethnomedicine; natural products; antibacterial; antimicrobial; Dominican Republic; tropical medicinal plants